Efek Hipoxia Mimetic Cobalt Chloride (CoC12 )terhadap Ekspresi mRNA dan Aktivitas Spesifik Manganese Superoksida Dismutase (Mn SOD ) Ginjal Tikus - Sandra, Yurika; Retno Prijanti, Ani; Inawati Wanandi, Septelia (Lembaga Penelitian Universitas YARSI, 2017)
MnSOD is a primary antioxidant that protects cells from oxidative stress due to H2O2 inmitochondrial membranes. This study aims to determine the effect of CoCl2 as hypoxic mimetic agent on mRNA expression of MnSOD and MnSOD-specific activity in rat kidney. Male Sprague dawley rat are induced with 30mg/Kg body weight CoCl2 intraperitoneally. After that, the experiment was divided into 3 groups: 2, 8, and 24 hours incubation after injection. All groups are compared with control group without injection. All of rat were terminated and the kidneys were removed. mRNA expression and specific activity of the kidney MnSOD are measured. After 2 hours, mRNA expression increased up to 42 times, after 8 and 24 hours return to normal. Specific activity of MnSOD in 2 hours after injection has not changed yet, and after 8 and 24 hours increased 1.5 times. This study shows that induction of Hipoxic mimetic CoCl2 enhances mRNA expression and MnSOD-specific activity.